Praktik Affiliate Marketing pada Platform E-commerce dalam Tinjauan Hukum Ekonomi Syariah - Fathur Rahman (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
Marketing that was traditionally (face to face) had changed to online marketing or through technological aids. The change in the marketing model was affiliate marketing. This affiliation practice in Indonesia was currently mostly carried out by online Marketplace. One of the Online Marketplaces that used the affiliate model was Shopee.co.id. when the modern transactions had developed and varied. It was necessary to maintain Islamic values ??so that they were still applied, so it was considered necessary to examine affiliate marketing practices from the perspective of Islamic law. Normative legal research, library research or document study is the research that focuses on written law. The practice of affiliate marketing cooperation carried out by Shopee with affiliate participants was permissible with several conditions in the principles of Islamic economic law. The commission practice carried out by Shopee and affiliate participants in Islam was identical to the samsarah and wakalah bil ujroh contracts.